IMPACT OF LIQUIDITY CREATION ON REAL ECONOMIC OUTPUT: EVIDENCE FROM FULL-FLEDGED ISLAMIC BANKS AND HYBRID CONVENTIONAL BANKS - Ismail, Izlin; Bacha, Obiyathulla Ismath; Mantai, Mohammed Mahmoud (Journal of Islamic Monetary Economics and Finance, 2024)
We examine the impact of the liquidity creation of Full-fledged Islamic Banks (FIBs) and Hybrid Conventional Banks (HCBs) on real economic output for a sample of 10 countries over the 11-year period from 2012–2022. Using the Feasible Generalized Least Squares (FGLS) framework, we show that both FIBs and HCBs liquidity creation per capita impact real economic output positively. However, HCBs have a greater impact on real economic output than FIBs. These results are statistically and economically significant. We further examine the impact of the liquidity created by both banking systems during the COVID-19 pandemic. Interestingly, for both bank types, liquidity creation has a negative impact on real output during the COVID-19 pandemic. However, in terms of magnitude, the negative impact is more pronounced for the HCBs. We also observe a non-linear impact of liquidity creation on real output, where the non-linearity is more pronounced among the HCBs. As for policy, our results imply that governments should incentivize FIBs to expand their scope and engage more in greenfield financing to have greater impact on real economic output.